Role of Matrix-Assisted Laser Desorption Ionization–Time-of-Flight Mass Spectrometry for Species Identification of Acinetobacter Strains - Krishnaraj, Anusha; Gupta, Pratima; Bhatia, Mohit; Omar, Balram Ji (Journal of Laboratory Physicians, 2023)
Introduction Acinetobacter species has become a leading cause of nosocomial infections in recent years.Objectives The aim of the study was to establish the usefulness of matrix-assisted laser desorption ionization–time-of-flight (MALDI-TOF) mass spectrometry (MS) for the identification of Acinetobacter species with respect to conventional biochemical methods and MicroScan WalkAway 96 Plus system and to compare the antibiotic susceptibility test results Kirby–Bauer disk diffusion method with MicroScan WalkAway 96 Plus automated identification and antimicrobial susceptibility testing system.Materials and Methods The study sample comprised 100 clinical isolates of Acinetobacter species. They were all identified using MALDI-TOF MS and compared with other two identification systems.Statistical Analysis Comparison of categorical variables by Fisher's exact test or Pearson's chi-square test was done. All statistical tools were two tailed, and a significant level p < 0.05 was used. All statistical tests were performed using SPSS v22.0 (Armonk IBM Corp., New York, United States). Cohen's kappa coefficients were also calculated and used as applicable.Results MALDI-TOF MS revealed 92 A. baumannii, 2 Acinetobacter nosocomialis, 3 Acinetobacter lwoffii, and 1 each was identified as Acinetobacter junii, Acinetobacter johnsonii, and Acinetobacter tandoii. There was moderate agreement between identification by MicroScan WalkAway and MALDI-TOF, and substantial agreement between conventional biochemical tests and MALDI-TOF. We found that there was a 100% categorical agreement with respect to susceptibility of aminoglycosides (amikacin, gentamicin, tobramycin) and cephalosporins (ceftazidime, cefepime, cefotaxime) between disk diffusion method and MicroScan WalkAway 96 Plus system. Total of 16 errors were observed.Conclusion Although MALDI-TOF MS could be useful to identify A. baumannii but not other species in the genus, it is a rapid, reliable method and can be routinely used in clinical laboratories.
Keywords: Acinetobacter species; antibiotic sensitivity; MALDI-TOF; MicroScan